Analysis Of Corporate Criminal Responsibility After The Enactment Of Law No. 1 Of 2023 On The Penal Code - Asis; Devi Mutiara Sanni (Law Research Review Quarterly, 2025)
This research aims to understand the concept of corporate criminal liability following the issuance of Law No. 1 of 2023 on the Criminal Code. Corporate criminal liability has become increasingly important due to the tendency of companies to engage in actions that harm society, the environment, or even their own employees. The research method used in this study is normative legal research with a legislative approach. Data were collected from primary and secondary sources related to corporate criminal liability. The research findings indicate that although Indonesia has Law No. 1 of 2023 on the Criminal Code, which includes provisions on criminal liability for corporations, there are still challenges in enforcing the law. Some of the challenges faced include the weak corporate awareness of social and environmental responsibility, as well as limitations in the role of law enforcement agencies in investigating and prosecuting corporate criminal acts. In this regard, efforts need to be made to enhance corporate awareness of social and environmental responsibility, as well as to improve the capacity of law enforcement agencies in handling corporate criminal acts. This research is expected to contribute to the development of corporate criminal law theory in Indonesia.